Effects of the Headteacher's Leadership in the Academic Performance of Students in Secondary Schools in Bondo Sub County, Kenya - Ogutu, Maurice Adera (JOOUST, 2014)
The difference in students' academic performance can be attributed to a number of factors; students' entry level, discipline, resources and key among them is the role of the Head teacher. One of the major responsibilities of the Head teacher is to promote academic performance of the school. The strategies that a school adopts in order to improve performance is dependent on the Head teacher. The purpose of this study is to assess the role of the Head teacher in the academic' performance of students in Secondary Schools in Bondo Sub county. The specific objectives of the study were to: assess the effects of the Head teachers' leadership styles in the students' academic performance, determine the level of involvement of the Head teacher in motivation of teachers and students in the academic performance of students and to assess the effects of the Head teacher's supervisory styles on instructional programmes on the students' academic performance. The conceptual framework adapted from Education Production Theory was used to establish the relationship between the dependent and independent variables. From the literature reviewed, most studies show that the Head teacher plays an important role in determining the academic performance in school. The study adopted saturated, purposive and simple random sampling technique to select the sample. The respondents were, the Head teachers, the Heads of departments and Form three students. Questionnaires for HODs, Form three Students and the interview schedule for Head Teachers were used as instruments of data collection. The research instruments were presented to two experts from the School of Education, Jaramogi Oginga Odinga University of Science and Technology for validation. To ascertain the reliability of the questionnaires, a pilot study was conducted in 10% of the sampled population which were then excluded in the actual data collection. The data collected were analysed using descriptive statistics which were then presented in form of tables and charts. The study found out that Head teachers had a role in improving the academic performance of the students through adopting a democratic form of leadership, motivation of students and teachers and in supervision of the curriculum content and delivery. Findings of the study are significant for example, on the theoretical value it contributes to greater insights into factors that contribute to total management. On practical value the study may serve as a reference point and enlighten Head teachers on appropriate management skills that may lead to improvement of student's performance in national examinations. Besides the findings may enlighten the administrators of the poor performing secondary schools in Bondo Sub county on how to improve student's achievement in national examinations. It is recommended that the Ministry of Education should adopt programs under KESI to train Teachers, Deputy Head teachers and Head Teachers on ways of fostering democratic leadership and its importance; the schools should embed and document in their strategic plans, programs of motivating teachers and students. That teachers should be provided with rightful duties and responsibilities and the ministry of Education through the Sub County Quality Assurance Officers should monitor to ensure that the Head teachers are active in monitoring the curriculum content and delivery so as to ensure that the set Education standards by the Ministry of Education are met.